The Influence of Financial Inclusion, Financial Literacy, and Financial Technology on The Financial Performance of MSMEs in Gunungkidul District - Novi Puspitasari; Pristin Prima Sari; Ratih Kusumawardhani (PT SOLUSI EDUKASI BERDIKARI, 2025)
This study looks at how the financial performance of MSMEs in Gunungkidul Regency is affected by financial inclusion, financial literacy, and financial technology. Purposive sampling is the research methodology employed in this study. The R2, T, and F-Tests are used in this study for test hypotheses. The study's findings show that the financial success is significantly and favorably impacted by the financial inclusion variable, with a regression coefficient value of 6,675 and a significance value of 0,0000 < 0,05. As evidenced by its value of 6,242 and significance value of 0,0000 < 0,05; the financial literacy variable has a significant and favorable impact on financial performance. Financial technology also has a significant and beneficial impact, with a value of 3,187 and a significance value of 0,002 < 0,05.